DAMPAK PENERAPAN INDONESIA-JAPAN ECONOMIC PARTNERSHIP AGREEMENT TERHADAP EKSPOR INDONESIA KE JEPANG - Izma Khairanisa Harahap; Astrid Maria Esther (Media Ekonomi, 2015)
This thesis is discussing about the effect of Indonesia Japan Economic Partnership agreement application for Indonesia's export to Japan in the period from 1991:1 until 2013:4. The variables which used is export, GDP, REER FDI exchange rate between Indonesia and Japan. The method which used in this thesis is Error Correction Model (ECM) model. The purpose of this research is to know about the relationship between export, GDP, REER and FDI also the influence of that variables in short term or long term. In addition, the purpose of this research also to know about how far the influence of Indoesia’s participation in Indonesia Japan Economic Partnership Agreement Indonesia Japan Economic Partnership Agreement. The result from ECM method, obtained that Indonesia's participation in Indonesia Japan Economic Partnership Agreement Indonesia Japan Economic Partnership Agreement doesn't have influence in short term or long term. And Japan's GDP variables that have the most significant influence in Indonesia's export to Japan develop